A exigibilidade de empreendimentos agrícolas inscreverem os imóveis utilizados mediante arrendamento no Cadastro Ambiental Rural para obtenção de licença ambiental - Borges, Wendel Rosa (2016)
Rural Environmental Registry – RER (in Portuguese, Cadastro Ambiental Rural – abbreviated “CAR”) is a legal institution established by the Federal Brazilian Act No. 12,651/2012 (usually referred to as "new Forest Code") for recording protected areas of all rural properties in Brazil, as well allow his georeferenced monitoring. However, the survey also addressed the relative uncertainty, due to the wording of the legal provision that establish and regulate the RER, specifically about the possibility of being granted environmental licensing of unregistered real estate, when there is a intent to locate the enterprise subject of license in the property under farm lease; i.e., with no real relation of property nor animus sibi habendi on the land. From this point emerged the discussion, if registration may be mandatory in these cases, since the legal requirement is targeted to owners and rural possessors. Therefore, a consideration about the rules and principles of the Brazilian Constitution and legislation was made to clarify the interpretation of the regulatory provisions of the RER, as its systematic purpose in Brazilian law, especially under the influence of environmental constitutional rights.